High admission prevalence of fluoroquinolone resistance in third-generation cephalosporin-resistant Enterobacteriaceae in German university hospitals. (27th February 2018) - Rohde, Anna M; Wiese-Posselt, Miriam; Zweigner, Janine; Schwab, Frank; Mischnik, Alexander; Seifert, Harald; Gastmeier, Petra; Kern, Winfried V
Abstract: Objectives: Fluoroquinolone resistance (FQR) in third-generation cephalosporin-resistant Enterobacteriaceae (3GCRE) presents serious limitations to antibiotic therapy. The aim of this study was to investigate whether the FQR proportion among 3GCRE differs between community-acquired (CA) and hospital-acquired (HA) isolates. Methods: In a prospective observational study covering 2014 and 2015, we monitored the occurrence of 3GCRE in adult hospitalized patients in six German university hospitals. 3GCRE clinical isolates were subdivided into CA and HA. Multivariable analysis identified factors associated with in vitro non-susceptibility to ciprofloxacin. Results: The dataset included 5721 3GCRE isolates of which 52.9% were HA and 52.7% exhibited FQR. Interestingly, the FQR proportion was higher in CA 3GCRE than in HA 3GCRE (overall, 60.1% versus 46.2%, respectively, P  <   0.001). Multivariable analysis adjusting for age confirmed community acquisition as a risk factor for FQR [adjusted rate ratio (aRR) 1.33, 95% CI 1.17–1.53]. Escherichia coli and Klebsiella spp. were associated with a much higher FQR proportion than other Enterobacteriaceae species (aRR 8.14, 95% CI 6.86–9.65 and aRR 7.62 with 95% CI 6.74–8.61, respectively). Conclusions: The high FQR proportion observed among CA 3GCRE, particularly in E. coli and Klebsiella spp., indicates that selection pressure in the outpatient setting needs to be addressed with antibiotic stewardship and other interventions in order to limit further spread of MDR.